PPARα is down-regulated following liver transplantation in mice - Nakagawa, Kan (J Hepatol, 2011)
BACKGROUND & AIMS: Graft dysfunction is one of the major complications after liver transplantation, but its precise mechanism remains unclear. Since steatotic liver grafts are susceptible to post-transplant dysfunction, and peroxisome proliferator-activated receptor (PPAR) α plays an important role in the maintenance of hepatic lipid homeostasis, we examined the role of PPARα in liver transplantation. METHODS: Livers were harvested from Sv/129 wild-type (Ppara(+/+)) mice and PPARα-null (Ppara(−/−)) mice and transplanted orthotopically into syngeneic Ppara(+/+) mice. RESULTS: Hepatocellular damage was unexpectedly milder in transplanted Ppara(−/−) livers compared with Ppara(+/+) ones. This was likely due to decreased lipid peroxides in the Ppara(−/−) livers, as revealed by the lower levels of fatty acid oxidation (FAO) enzymes, which are major sources of reactive oxygen species. Hepatic PPARα and its target genes, such as FAO enzymes and pyruvate dehydrogenase kinase 4, were strongly down-regulated after transplantation, which was associated with increases in hepatic tumor necrosis factor-α expression and nuclear factor-κB activity. Inhibiting post-transplant PPARα down-regulation by clofibrate treatment markedly augmented oxidative stress and hepatocellular injury. CONCLUSIONS: Down-regulation of PPARα seemed to be an adaptive response to metabolic alterations following liver transplantation. These results provide novel information to the understanding of the pathogenesis of early post-transplant events.